Pengalokasian Produk pada Ruang Rak Displai Gerai Minimarket Menggunakan Multilevel Association Rules - Mirna Lusiani (Universitas Bunda Mulia, 2017)
Product allocation and product assortment have a significant influence on customer buying behavior. With limitation on shelf space, retailer must determine the customer buying behavior to maximize the profit for retailer. This research is focused on the products shelf space allocation based on the association between product categories and subcategories using data mining technique, multilevel association rules. Takes advantage of data transactions, 4 associations between categories and 11 associations between subcategories products were obtained. The degrees of activity relationship between categories from 4 associations obtained by Activity Relationship Chart method. The result, product allocation configuration based on the associations between product categories and degree of activity relationship is shown.Keywords: Product Allocation, Data Mining, Multilevel Association Rules, Activity Relationship Chart